Representations of Violence and Views Toward Men in Nawal El Saadawi's Novel Woman at Point Zero: Simone de Beauvoir Perspective - Fatiya Aulia Muthmainnah; Rinta Arina Mansikana (Jogjakarta Communication Conference (JCC), 2026)
Violence against women is a social issue that does not only occur in real life but is also reflected and constructed through literary works as cultural texts. From the perspective of communication studies, the novel is understood as a medium that actively produces and represents meanings about gender relations to its audience. This study examines the representation of violence experienced by the character Firdaus and her views toward men in Nawal El Saadawi's novel Woman at Point Zero. Employing a descriptive qualitative approach through library research and document analysis, this study analyzes selected excerpts categorized into two groups: excerpts depicting Firdaus's experiences of violence and excerpts reflecting her views toward men. The analysis was conducted using Stuart Hall's theory of representation through a constructionist approach encompassing the conceptual system and the language system, as well as Simone de Beauvoir's existential feminism through the concepts of The Other and immanence-transcendence. The findings reveal that Woman at Point Zero represents the violence experienced by Firdaus as a systematic and structural pattern that permeates multiple institutional domains family, marriage, personal relations, and the state perpetrated by different male figures yet consistently constructing the same knowledge: that Firdaus's subordinate position as an object is normalized across all layers of society. This cross-institutional accumulation of violence drives Firdaus's existential journey from immanence as a passive The Other toward transcendence as a critically conscious subject, manifesting in six progressive dimensions of her views toward men from existential anger to total structural rejection of the patriarchal system.